2010
DOI: 10.2135/cropsci2008.07.0447
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Panicle Blight Resistance QTLs in Rice and Their Association with Other Disease Resistance Loci and Heading Date

Abstract: Bacterial panicle blight (BPB) of rice (Oryza sativa L.) occurs when the bacterium Burkholderia glumae Kurita and Tabei infects emerging and flowering panicles, causing kernels to abort. To identify quantitative trait loci (QTLs) for BPB resistance, a population of 300 recombinant inbred lines (RILs) derived from a cross between ‘Lemont’ and ‘TeQing’ were evaluated in 2001 and 2002 in field plots spray‐inoculated with B. glumae at the time of flowering. Because this RIL population had been previously used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 37 publications
3
57
1
Order By: Relevance
“…Hoshikawa (1989) provides a lengthy description of rice plant growth, including tiller production. 1999TN 2002TN 2003TN 1998N1T 1999N1T 2002N1T 2003N1T 1998 (1998, 1999, 2002, and 2003) per panicle (Li et al, 1997); panicle weight (Li et al, 1998); tiller angle (Li et al, 1999b); disease resistance (Pinson et al, 2005(Pinson et al, , 2010 Mutations: OsmiR393, Xia et al, 2012QTLs: Wang et al, 1994Yan et al, 1998;nagata et al, 2002;Xing et al, 2002;Ramalingam et al, 2003;Miyamoto et al, 2004;Zhang et al, 2005; Blast resistance (Tabien et al, 2002); 100-kernel weight (Paterson et al, 1995;Li et al, 1997); grain no. Pearson correlations between four Lemont ´ TeQing recombinant inbred line (LT-RIL) observation trials (years) and between traits potentially associated with the primary trait of interest, the max.…”
Section: Relationship Between Tiller Production and Rapid Seedling Dementioning
confidence: 99%
See 1 more Smart Citation
“…Hoshikawa (1989) provides a lengthy description of rice plant growth, including tiller production. 1999TN 2002TN 2003TN 1998N1T 1999N1T 2002N1T 2003N1T 1998 (1998, 1999, 2002, and 2003) per panicle (Li et al, 1997); panicle weight (Li et al, 1998); tiller angle (Li et al, 1999b); disease resistance (Pinson et al, 2005(Pinson et al, , 2010 Mutations: OsmiR393, Xia et al, 2012QTLs: Wang et al, 1994Yan et al, 1998;nagata et al, 2002;Xing et al, 2002;Ramalingam et al, 2003;Miyamoto et al, 2004;Zhang et al, 2005; Blast resistance (Tabien et al, 2002); 100-kernel weight (Paterson et al, 1995;Li et al, 1997); grain no. Pearson correlations between four Lemont ´ TeQing recombinant inbred line (LT-RIL) observation trials (years) and between traits potentially associated with the primary trait of interest, the max.…”
Section: Relationship Between Tiller Production and Rapid Seedling Dementioning
confidence: 99%
“…number of tillers produced per potted 9-wk seedling. per panicle (Li et al, 1997); disease resistance (Li et al, 1999a;Pinson et al, 2005Pinson et al, , 2010 Mutations: tillering and dwarf 1 (tad1), Xu et al (2012). tiller number per plant (TN), node of first tiller (N1T), average number of seed-bearing panicles per plant (observed only from the 1998 trial), and average number of leaves (nodes) produced by 8-wk-old seedlings (SLN).…”
Section: Relationship Between Tiller Production and Rapid Seedling Dementioning
confidence: 99%
“…We tested Nona Bokra and found that it was not resistant to grain rot (data not shown). In addition, the chromosomal position of qRBS1 is different from those of QTLs reported to be associated with resistance to grain rot (Mizobuchi et al 2013; Pinson et al 2010). Therefore, the factors associated with resistance to seedling rot and grain rot appear to be different.…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have been performed to understand the genetic control of resistance to bacterial grain rot and several cultivars appear to be resistant to bacterial grain rot (Goto and Watanabe 1975; Groth et al 2007; Imbe et al 1986; Mogi and Tsushima 1985; Nandakumar et al 2007a; Nandakumar and Rush 2008; Pinson et al 2010; Prabhu and Bedendo 1988; Sayler et al 2006; Sha et al 2006; Takita et al 1988; Wasano and Okuda 1994; Yasunaga et al 2002). Using resistant cultivars, QTLs for resistance to bacterial grain rot have been reported (Mizobuchi et al 2013; Pinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation